2022
DOI: 10.1007/s00265-022-03259-6
|View full text |Cite
|
Sign up to set email alerts
|

State and physiology behind personality in arthropods: a review

Abstract: In the endeavour to understand the causes and consequences of the variation in animal personality, a wide range of studies were carried out, utilising various aspects to make sense of this biological phenomenon. One such aspect integrated the study of physiological traits, investigating hypothesised physiological correlates of personality. Although many of such studies were carried out on vertebrates (predominantly on birds and mammals), studies using arthropods (mainly insects) as model organisms were also at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 186 publications
0
6
0
Order By: Relevance
“…Effect of state variables, such as body condition, on behavioural traits of an individual has been widely documented (Scharf, 2016; Rádai et al ., 2022), but empirical evidence for how such effects may vary with life-stage is sparse. In our study we used starvation to manipulate the body condition of larvae and adults in A. rosae .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of state variables, such as body condition, on behavioural traits of an individual has been widely documented (Scharf, 2016; Rádai et al ., 2022), but empirical evidence for how such effects may vary with life-stage is sparse. In our study we used starvation to manipulate the body condition of larvae and adults in A. rosae .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, a recent meta-analysis revealed that the effect of poor nutrition on risk-taking behaviour could be life-stage dependent, with juveniles showing stronger responses and higher risk-taking behaviour in low-nutrition conditions while the effect on adults was less unequivocal (Moran et al ., 2021). Life stage-specific effects on behaviour have been documented in previous studies (Polverino et al ., 2016; Rádai et al ., 2022), although few studies have documented such effects in holometabolous insects which occupy distinct niches in the juvenile and adult stage. The need to adjust to conditions of lower food availability may lead to individualised niche conformance (as defined in Müller et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, whether positive or negative feedback predominates within populations depends on the selective landscape [5]. This context-dependent selection on individual state may explain the observed weak associations between intrinsic states (such as metabolic rate (MR), plasma hormone levels or body mass) and personality in recent meta-analytic reviews [6][7][8]. For example, Belgrad et al [9] demonstrated that boldness in mud crabs was positively correlated with short-term energy storage during the early spawning season, but negatively correlated with long-term energy storage during the later spawning season.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, GCs may serve as an important mediator of the feedback between MR and personality [30,31]. However, the causal relationships between MR, GCs and personality remain unclear [7,32]. One possibility is that GCs affect energy metabolism, which in turn affects personality, resulting in the MR-personality association [10,32].…”
Section: Introductionmentioning
confidence: 99%